Indigenous Populations of Costa Rica and Their Access to Higher Education. Rural Education Division: A Training Alternative - Vivian Carvajal-Jiménez; Kenneth Alfredo Cubillo-Jiménez; Marielos Vargas-Morales (Revista Electrónica Educare)
The following text describes the historical and operational evolution of inclusive actions in education directed towards indigenous populations in Costa Rica, one of the most vulnerable and discriminated groups in the country. This article specifically underlines how the national higher education and laws have evolved toward acknowledging the inalienable rights of these ancient peoples. The work done by the Universidad Nacional [National University of Costa Rica], specifically by the Rural Education Division (DER, in Spanish), stands out with roving degree courses and trainers of teachers for the General Basic Education being offered in the rural and indigenous contexts where students live. Part of the analysis includes a review of the barriers for accessing the university environment, as well as the role of public universities in democratizing higher education. The conclusion is that Costa Rica has made significant progress in the fields of law, administration, and pedagogy regarding access to education for the indigenous peoples; notwithstanding, these shall not be deemed as concluded achievements concerning the rights of the original peoples as there is a long way to go yet for asserting an equitable offering for them.